Assessment of adhesion, invasion and cytotoxicity potential of oral Staphylococcus aureus strains. (September 2015) - Merghni, Abderrahmen; Ben Nejma, Mouna; Helali, Imen; Hentati, Hajer; Bongiovanni, Antonino; Lafont, Frank; Aouni, Mahjoub; Mastouri, Maha
Abstract: The oral cavity is regarded as a relevant site for Staphylococcus aureus colonization. However, characterization of virulence mechanisms of oral S. aureus remains to be uncovered. In this study, twenty one S. aureus strains isolated from the oral cavity of Tunisian patients were screened for adherence, invasion and cytotoxicity against HeLa cells. In addition, the presence of adhesins ( ica A, ica D, can, fnb A and fnb B) and α-hemolysin ( hla ) genes in each strain was achieved by polymerase chain reaction (PCR). Our finding revealed that oral S. aureus strains were able to adhere and invade epithelial cells, with variable degrees (P < 0.05). Moreover they exhibited either low (23.8%) or moderate (76.2%) cytotoxic effects. In addition 76.2% of strains were ica A and ica D positive and 90.5% harbor both the fnb A and the fnb B gene. While the cna gene was detected in 12 strains (57.2%). Furthermore, the hla gene encoding the α-toxin was found in 52.4% of the isolates. All these virulence factors give to S . aureus the right qualities to become a redoubtable pathogen associated to oral infections. Highlights: Adhesion, invasion and cytotoxicity of oral Staphylococcus aureus strains were investigated. Prevalence of adhesins and α-toxin genes was analyzed. Oral S. aureus were able to adhere to and invade HeLa cells. Oral S. aureus showed different levels of cytotoxicity. Oral S. aureus harbor a large number of adhesins and exotoxins encoding genes.